PELATIHAN PENGOLAHAN KASUMBA TURATE SEBAGAI IDE LOKAL BERWIRAUSAHA BAGI MAHASISWA UNIVERSITAS PATOMPO - St. Rahmadani; Sifli Marlina, Syahruni Karim (JOURNAL OF COMMUNITY DEDICATION, 2023)
The people of South Sulawesi in general are an area that uses Kasumba Turate flower petals as a local medicine, but the use is still very simple, namely just brewing it with warm water to treat smallpox. According to scientific research, this plant contains antioxidants and contains various substances that are beneficial for body fitness. This service is based on opening the horizons of knowledge and business ideas made from local ingredients for Patompo University students, namely Kasumba Turate. The solution is to provide outreach and training regarding the processing of the Kasumba Turate plant into an ingredient in various healthy drinks and foods. The output target to be achieved is increasing the knowledge of Patompo University students about how to process Kasumba Turate flower petals in a more varied way. This training is divided into three parts, namely knowledge about the contents and benefits of Kasumba Turate, training on making ready-to-brew tea and kombucha tea, and healthy pudding. It is hoped that this information can then be distributed to the surrounding community. From the results of the activities carried out, it can be seen that the participants who took part in community service activities (PKM) felt enthusiastic about taking part in the activities and were motivated to start a business using Kasumba Turate raw materials.